PEMBERDAYAAN KELOMPOK GURU MELALUI PEMBELAJARAN BERBASIS KEARIFAN LOKAL - Desy Safitri; Sujarwo, Sujarwo; Nurzengky Ibrahim; Arita Marini; Musril Zahari (JURNAL PENGABDIAN MANDIRI, 2024)
Empowering groups of teachers through learning based on local wisdom is an important step in building student awareness about the need to maintain and protect the environment. By involving local wisdom, students will be able to recognize and appreciate the natural and cultural diversity around them. In the context of environmental preservation, teacher groups are empowered which has implications for creating a young generation who cares and is responsible for the future of the environment.